1989
DOI: 10.1093/oxfordjournals.jbchem.a122702
|View full text |Cite
|
Sign up to set email alerts
|

Control of Influenza Virus Gene Expression: Quantitative Analysis of Each Viral RNA Species in Infected Cells

Abstract: We established a quantitative hybridization system by which three types of influenza virus RNAs (vRNA, mRNA, and cRNA) for the 8 genome segments were measured individually. As the hybridization probes, 32P-labeled RNAs of both plus and minus polarity were produced employing an SP-6 transcription system and used in a large molar excess, sufficient to overcome complementary RNAs present in the viral RNA samples. Employing the system, we studied the control of the synthesis of each viral RNA species in MDCK cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
94
3

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 0 publications
18
94
3
Order By: Relevance
“…The dependence of IFV virus export on the CRM1 pathway is well established and the TAP pathway has also been shown to be involved in IFV export [31]. In addition, several studies indicate specific inhibition of late viral gene expression after UV irradiation, LB, actinomycin D or DRB treatment [1,12,21,22,27]. These studies reported that the drugs DRB and LB, which were added at the beginning of the infection, did not inhibit viral mRNA synthesis completely and that viral transcripts were retained in the nucleus, consistent with our microscopy results.…”
Section: Discussionmentioning
confidence: 99%
“…The dependence of IFV virus export on the CRM1 pathway is well established and the TAP pathway has also been shown to be involved in IFV export [31]. In addition, several studies indicate specific inhibition of late viral gene expression after UV irradiation, LB, actinomycin D or DRB treatment [1,12,21,22,27]. These studies reported that the drugs DRB and LB, which were added at the beginning of the infection, did not inhibit viral mRNA synthesis completely and that viral transcripts were retained in the nucleus, consistent with our microscopy results.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting RNA was extracted again with phenol-chloroform. A quantitative hybridization system was employed to measure the amount of the three types of virus-specific RNA (mRNA, cRNA and vRNA) for each of the eight genome segments as reported elsewhere (Hatada et al, 1989), in which RNA probes intensely labelled with 32p were used in a molar excess sufficient to overpower complementary RNAs present in the viral RNA samples. The probes for mRNA and cRNA were obtained by transcribing SP 6 recombinant DNAs, which gave the intact 5' end sequences of vRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been carried out to reveal the relationship between the synthesis of viral RNAs and proteins (Lamb & Choppin, 1976;Hay et al, 1977b;Inglis & Mahy, 1979;Barrett et al, 1979;Smith & Hay, 1982;Enami et al, 1985 ;Shapiro et al, 1987;Hatada et al, 1989). In MDCK cells infected with A/Udorn/72 (H3N2) virus, the synthesis of virus-specific RNAs proceeds as follows (Hatada et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it was concluded that there must be some form of segment specificity in genome packaging (Laver & Downie, 1976;Nakajima & Sugiura, 1977). Further support was lent to the segment-specific packaging model by the observation that segments were present at equimolar levels in virions (Hatada et al, 1989;McGeoch et al, 1976) even when their ratios in infected cells differed (Bergmann & Muster, 1995;Smith & Hay, 1982), suggesting that some form of selection process was operating.…”
Section: Genome Segmentation: a Mixed Blessingmentioning
confidence: 99%